Pengaruh Kepemimpinan Transformasional, Komitmen Organisasi, dan kepuasan kerja Terhadap Organizational Citizenship Behavior (OCB) pada Karyawan SuperDazzle - Arista Natia Afriany; Rika Apriliani (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
The purpose of this study was to determine the effect of transformational leadership, organizational commitment, and job satisfaction on organizational citizenship behavior (OCB) among SuperDazzle employees. This research was conducted at SuperDazzle from May to December 2022. This research is a quantitative research using SPSS software version 24.0. The population in this study were all SuperDazzle employees with a total sample of 80 people using the saturated sampling method. Methods of data collection using a questionnaire. The analytical method used is multiple linear regression analysis. The results showed that transformational leadership had a positive and significant effect on OCB, organizational commitment had a positive and significant effect on OCB, job satisfaction had a positive and significant effect on OCB. The results of the study show that transformational leadership, organizational commitment, and job satisfaction simultaneously influence OCB. The adjusted R-squared value was 53.9 percent and the remaining 46.1 percent was explained by other variables not included in this study.